Sequential Transplantation of Haploidentical Stem Cell and Unrelated Cord Blood With Using ATG/PTCY Increases Survival of Relapsed/Refractory Hematologic Malignancies - Li, Hua; Li, Xiaofan; Chen, Yiling; Li, Duihong; Chen, Xianling; Zhu, Zhijuan; Wang, Yiting; Huang, Jiafu; Chen, Ping; Chen, Yuanzhong; Li, Nainong (Frontiers in Immunology, 2021)
Allogeneic haploidentical HSCT (haplo-HSCT) and unrelated umbilical cord blood transplantation（UCBT）are used in patients lacking HLA-identical sibling or unrelated donors. With myeloablative condition and GVHD prophylaxis of using low dose ATG and post-transplantation cyclophosphamide (PTCY), we conducted a prospective clinical trial. Of eligible 122 patients from February 2015 to December 2019 in the study, 113 patients were involved. 48 patients were in the group of sequential haplo-cord transplantation (haplo-cord HSCT), 65 patients were in the group of single UCBT. The primary endpoint of 2-year disease-free survival (DFS) was no statistical difference between groups (64.1% vs. 56.5%), p＞0.05. The analysis of subgroup patients with relapsed/refractory showed haplo-cord HSCT was associated with better OS（HR 0.348, 95% CI, 0.175-0.691; p=0.0025）, DFS （HR 0.402, 95% CI, 0.208-0.779; p=0.0069）and GRFS （HR 0.235, 95% CI, 0.120-0.457, p＜0.0001）compared single cord group. The 2 -year’s probability in OS，DFS, GRFS was 64.9% vs. 31.6% ，64.5% vs. 31.6% ，and 60.8% vs. 15.0% in the haplo-cord group and single cord group，respectively. III-IV acute GVHD 8.3% vs. 6.2%, chronic GVHD 25.8% vs. 13.7%, and extensive chronic GVHD 5.3% vs. 1.8% were shown in corresponding group， p>0.05. The patients engrafted persistently with UCB showed better survival outcomes. Our sequential Haplo-cord HSCT with ATG/PTCY improved the survival of patients and might be an alternative transplantation approach for patients with relapsed/refractory hematologic malignancies.